The examination of the profitability and competitiveness regarding the energy plantations of woody plants in the region of Észak-Alföld - Csipkés, Margit (Applied Studies in Agribusiness and Commerce, 2012)
Due to the decrease in the quantity of traditional energy sources, in the future an alternative energy production should be sought which provides minimum environmental burden and offers an opportunity to generate energy. The use of biomass provides another option to resolve this problem. The most important features of the biomass are that the quantity doesn’t decrease during conversions and are reproduced by natural processes. The main raw materials of the biomass are considered to be the energy plantations, which are economic in areas where the farmer, during the traditional production, can’t or with difficulties can cover the expenses, so that profitably sustainable cultivation branches can come to the forefront with less material and energy input. Those cases in which the cultivation of agricultural areas are not economically feasible, there is a possible utilization in our country which is the installation of plantations with energetic aim.